KONSEP KEPEMILIKAN DALAM ISLAM - Pratanto Rahayu, Wedi (Irtifaq, 2020)
Abstract: This article discusses the concept of ownership in Islam. In the concept of Islamic ownership, the management of large and vast natural resources has become more organized. Islam teaches the concept of limitations in property ownership, but does not eliminate the right of individual ownership of an object. The concept of Islam in public and state ownership provides comfort and prosperity to all levels of society because with good state management of natural resources can be distributed to each individual in a guaranteed and appropriate manner. The implimentation of the ownership concept in Islam will be able to achieve justice, a principle in Islam not only justice for individuals but also overall for all people. Keywords: Concept, Ownership, justice